Rare bird documentation form for Northern Goshawk at Seven Bridges Park, 1981 - Myers, Robert K.et al (1981)
Rare bird documentation form for a Northern Goshawk at Seven Bridges Park in Bremer County, IA on November 21, 1981. Epson - sheet feed